Tetrazine‐Based Metal‐Organic Frameworks as Scaffolds for Post‐Synthetic Modification by the Click Reaction. Issue 5 (22nd January 2020) - Vinu, Madhan; Sivasankar, Kulandaivel; Prabu, Samikannu; Han, Jeng‐Liang; Lin, Chia‐Her; Yang, Chun‐Chuen; Demel, Jan
Abstract : Metal‐organic frameworks are one of the most active research fields today. Despite the progress in recent years, synthesis of highly porous structures bearing functional groups for specific applications remains a challenge. Here, we describe synthesis of Zr(IV) and Hf(IV)‐based tetrazine containing metal‐organic frameworks, ZrTz‐68 and HfTz‐68 with pore size of 2.1 nm, specific surface area up to 4217 m 2  g –1, and a UiO‐68 topology. The synthesis can be done on a multi‐gram scale from inexpensive linker 4, 4'‐(1, 2, 4, 5‐tetrazine‐3, 6‐diyl)dibenzoic acid (H2 TzDB). Moreover, because of the π‐conjugated tetrazine groups these MOFs can be easily post‐synthetically modified by a "click" reaction maintaining the crystallinity of the framework. Due to the diversity of "clickable" substituents, this strategy represents highly versatile tool for a wide range of applications. Abstract : The π‐conjugated tetrazine containing metal‐organic frameworks ZrTz‐68 and HfTz‐68 with pore size of 2.1 nm and specific surface area up to 4217 m 2  g –1 were prepared. MOFs can easily be post‐synthetically modified by a "click" reaction maintaining the crystallinity and the stability of the framework.